The Effectiveness of The “Sentuh Tanahku” App in The “Sertifikatku” Service at The Cirebon City Land Agency - Kalya Sabina; Iskandar Zulkarnaen (Publik : (Jurnal Ilmu Administrasi), 2026)
The goal of this study is to assess and investigate the effectiveness of the Sentuh Tanahku application’s implementation as a form of e-governance transformation in the Cirebon City Land Office’s Sertifikatku service. This study employs a qualitative methodology, gathering data via document analysis, in-depth interviews with relevant informants, and field observations. Effectiveness was measured using five dimensions of organizational effectiveness: resources, funding, facilities and infrastructure, quality and quantity, and time. According to the study’s findings, this application has effectively reduced public wait times at physical service counters and improved information transparency by utilizing an online queuing system. However, its implementation has not yet achieved maximum efficacy due to a number of challenges. In terms of resources, users low levels of digital literacy, especially among the elderly, lead to a high reliance on staff assistance at the service. Significant problems with digital infrastructure also exist, including errors in the system, poor synchronization of document movement data (slow status updates), and problems with verification codes (OTPs) not getting to email inboxes. In addition to lowering service quality, rigid complaint responses in the form of automated replies (robot templates) ultimately waste the public's time by requiring manual checks. In conclusion, this digital innovation greatly promotes transparency in land administration; however, in order to achieve the goal of effective public service, it urgently needs more dependable server infrastructure maintenance from the federal government and the thorough implementation of digital literacy education programs at the local level.